Glucose-6-phosphate reduces calcium accumulation in rat brain endoplasmic reticulum - Cole, Jeffrey T.; Kean, William S.; Pollard, Harvey B.; Verma, Ajay; Watson, William D. (Frontiers in Molecular Neuroscience, 2012)
Brain cells expend large amounts of energy sequestering calcium (Ca2+), while loss of Ca2+ compartmentalization leads to cell damage or death. Upon cell entry, glucose is converted to glucose-6-phosphate (G6P), a parent substrate to several metabolic major pathways, including glycolysis. In several tissues, G6P alters the ability of the endoplasmic reticulum to sequester Ca2+. This led to the hypothesis that G6P regulates Ca2+ accumulation by acting as an endogenous ligand for sarco-endoplasmic reticulum calcium ATPase (SERCA). Whole brain ER microsomes were pooled from adult male Sprague-Dawley rats. Using radio-isotopic assays, 45Ca2+ accumulation was quantified following incubation with increasing amounts of G6P, in the presence or absence of thapsigargin, a potent SERCA inhibitor. To qualitatively assess SERCA activity, the simultaneous release of inorganic phosphate (Pi) coupled with Ca2+ accumulation was quantified. Addition of G6P significantly and decreased Ca2+ accumulation in a dose-dependent fashion (1-10 mM). The reduction in Ca2+ accumulation was not significantly different that seen with addition of thapsigargin. Addition of glucose-1-phosphate or fructose-6-phosphate, or other glucose metabolic pathway intermediates, had no effect on Ca2+ accumulation. Further, the release of Pi was markedly decreased, indicating G6P-mediated SERCA inhibition as the responsible mechanism for reduced Ca2+ uptake. Simultaneous addition of thapsigargin and G6P did decrease inorganic phosphate in comparison to either treatment alone, which suggests that the two treatments have different mechanisms of action. Therefore, G6P may be a novel, endogenous regulator of SERCA activity. Additionally, pathological conditions observed during disease states that disrupt glucose homeostasis, may be attributable to Ca2+ dystasis caused by altered G6P regulation of SERCA activity